Analysis of the role of packaging design on brand identity with a case study of Sukabumi souvenirs “MOCHI” lampion - Pratama S Mohammad Iqbal Faiz; Nugraha Rifky; Istianah Raray (BIO Web of Conferences)
Indonesia has a very diverse cultural diversity, customs, dances, languages, folk songs, special foods, and so on. Among these variations, one of the interesting cultures is the diversity of traditional foods from various ethnic groups in Indonesia. All regional tribes in Indonesia have their own characteristics in traditional types, technology, and food packaging. In general, regional culinary products are categorized in the form of micro, small and medium enterprises (MSMEs). Maflahah (2012) states that most MSME product packaging does not have an attractive, innovative and creative design. Food products that are only wrapped in transparent plastic without any labels or descriptions give an unattractive impression. MSME products must have an attractive packaging design, because one of the most important elements in product visuals is packaging. Most MSME product packaging does not have a visual element of the product in the packaging, compared to products from companies that have large capital, so the selling value and attractiveness are very This study will analyze the role of packaging design and exposure to the extent to which a packaging design is able to convey a final message/communication from producers to consumers, through semantic analysis of a product to a product identity of a product Sukabumi “Mochi Kaswari Lampion”.